INTEGRATING IOT AND MOBILE APPLICATIONS FOR EFFICIENT PLANT WATERING: THE IOT SMART WATERING SYSTEM (SWS) (Journal of Digital System Development, 2024)
The Internet of Things (IoT) is the connection with networks and devices that can exchange data through the Internet without human intervention.  A mobile application is a software system that runs on a mobile device.  The absence of smart detection in the existing system is insufficient for watering the plantation. This brought some problems, as no one knew about the condition of the plantation, and caused overwatering and under-watering problems. Therefore, combining IoT concepts and mobile applications has adapted to make the system a more innovative automated system. The IoT Smart Watering System (SWS)” focuses on building an intelligent watering system that will sense the humidity of the soil and the temperature of the environment using the sensor. Then, the data will be sent to the user’s mobile application using the internet to allow users to view it. The objective of this project is to let the user know about the condition of the plant and smart watering based on the condition. Compared with the existing system, the advantage of this system is that the user can automatically monitor the status of the data from mobile phones. This system is developed for everybody who wishes to have this system, such as homeowners, farmers, and students using an Android mobile device. In this project, the waterfall method was implemented as a software development process to ensure the successful development of the system and meet the user’s requirements. The existence of the IoT Smart Watering System will benefit society by preventing the waste of water and minimizing human intervention. This could save users time and enhance the watering plant's effectiveness. In the future, a notification and view data graph feature will be integrated into this system.